Chemothermally Driven Out‐of‐Equilibrium Materials for Macroscopic Motion. Issue 6 (8th June 2020) - Muradyan, Hurik; Guan, Zhibin
Abstract: In nature, living systems operate far from equilibrium by consuming and dissipating energy to perform vital processes. Biological systems use chemically derived energy to power out‐of‐equilibrium processes to generate complex macroscopic motion by dissipating energy at the molecular scale. In contrast, it remains a major challenge to create synthetic out‐of‐equilibrium systems that operate on the macroscopic scale. Herein we report a chemically fueled out‐of‐equilibrium system that can perform macroscopic actuation and do work by lifting objects. We achieve this by driving a lower critical solution temperature (LCST) transition of poly( N ‐isopropylacrylamide) (pNIPAAm) hydrogels with heat generated by a copper‐catalyzed azide‐alkyne cycloaddition (CuAAc) reaction. Upon completion of the reaction, heat dissipates to the environment, and the system returns to equilibrium, completing one cycle of out‐of‐equilibrium behavior, which can be repeated for multiple cycles by adding new chemical fuels. Abstract : Pumping iron : Mimicking biological out‐of‐equilibrium systems, here a chemically fueled out‐of‐equilibrium material system was demonstrated to generate macroscopic motion such as actuation and lifting objects. This was achieved by driving a lower critical solution temperature (LCST) transition of poly(N‐isopropylacrylamide) (pNIPAAm) hydrogels with heat generated by a copper‐catalyzed azide‐alkyne cycloaddition (CuAAc) reaction.